LEARNING PREFERENCES AND VACCINATION STATUS OF STUDENTS IN A TERTIARY INSTITUTION: BASIS FOR FLEXIBLE LEARNING IMPLEMENTATION 2.0 - Ediric D. Gadia; John Mark R. Asio; Erlinda C. Abarintos; Darwin P. Paguio; Lovelyn P. Ceralde; Imelda D.P. Soriano (Universitas PGRI Madiun, 2022)
The objective of this study is to determine the learning preferences and vaccination status of students from a local college in Olongapo City, Philippines. The investigators employed a descriptive-survey research among 5,021 students who were currently enrolled in the academic year of 2021-2022. Results show that 94.7% prefer online mode of learning; 79.7% show intention to enroll for the next semester of the new academic year; however only 51.7% of the students wanted a face-to-face class and 61.4% of the students’ parents/guardian approve their son/daughter to attend face-to-face classes. In terms of vaccination status, 95.3% of the students have their vaccinations shots already (fully vaccinated) and Pfizer was the brand of choice of the 38% students. The study concluded that students are still prefer online mode of learning. Also, majority of the students were fully vaccinated. The study recommends continue and enhance the implementation of flexible learning of the institution.